The distribution and unexpected genetic diversity of the non-indigenous annelid Ficopomatus enigmaticus in California - Yee, Alison; Mackie, Joshua; Pernet, Bruno (Aquatic Invasions, 2019)
The non-indigenous annelid Ficopomatus enigmaticus has been established in San Francisco Bay since at least 1921, but in the past 30 years it has also been found in other parts of California. In the summer of 2017 we surveyed 136 sites to determine its current distribution in the state. We found F. enigmaticus at 23 sites ranging from San Francisco Bay in the north to Newport Bay in the south. Populations were concentrated in four regions: San Francisco Bay, Monterey Bay, Santa Barbara, and sites in Los Angeles and Orange Counties. Presence sites did not differ systematically in salinity or temperature from absence sites, but all presence sites appeared to have restricted exchange of water with nearby oceanic habitats. Data on the timing of first discovery in each region is roughly consistent with the hypothesis of southward spread of propagules from the San Francisco Bay population. To further test this hypothesis, we obtained mitochondrial DNA sequences from individuals collected from four sites nearly spanning the current latitudinal range of F. enigmaticus in California. Recent work from Australia suggests that there is substantial within-population cryptic genetic diversity in F. enigmaticus, with individual aggregations containing individuals whose mitochondrial cytochrome B haplotypes fall into one of two very distinct ( 19% uncorrected genetic distance) haplotype groups, Clades 1 and 2. We found a similar pattern in California, with Clade 1 and Clade 2 individuals co-occurring at two of the four sites we sampled. Three of ten known F. enigmaticus haplotypes occurring in Australia were observed in California populations; four haplotypes observed in California have not previously been reported. Analysis of haplotype distributions suggests that central California populations may be derived from the San Francisco Bay population, while unique haplotypes present in the Long Beach population suggest the possibility of a second independent introduction in that region. Additional genetic data from populations of F. enigmaticus around the globe are needed to resolve the invasion history and systematics of these widespread serpulids.
World Polychaeta Database (WPolyDb)